Niveau De Connaissance De La Ménopause Et Habitudes Alimentaire Et Médicinale Des Femmes En Côte d’Ivoire - Kouame Amoin Gervaise; Koffi Yao Mesmi; Piba Serge Cherry; Bakayoko Adama; Tra Bi Fézan Honora; KONE Mamidou Witabouna (European Scientific Journal, ESJ, 2018)
Menopause is accompanied by symptoms that are difficult for women to tolerate. In Asia, plants used by some women allow them to live well in menopause. The purpose of this study was to assess women's knowledge level of menopause and the diversity of local medicinal and food plants that they are accustomed to before this stage. A survey was conducted in the departments of Grand Lahou and Katiola with 267 women aged 40 to 70 using semistructured interviews. The results showed that the average age of menopause was 48.88 ± 4.19 years. In total, 96.85% of women considered that menopause is normal from the age of 50 and has no effect on health. For 90.94% of them, stopping menstruation during menopause is perceived as a release but difficult to withstand because of the disorders felt. The symptoms and risks of menopause were unknown respectively by 73.68% and 98.71% of women. Hot flashes were the best known. A variety of medicinal and food plants (47) are used by postmenopausal women who have no symptoms or very few symptoms of menopause. These plants may have an interest in controlling the symptoms of menopause.